A Chemosensory Protein BtabCSP11 Mediates Reproduction in Bemisia tabaci - Zeng, Yang; Merchant, Austin; Wu, Qingjun; Wang, Shaoli; Kong, Lan; Zhou, Xuguo; Xie, Wen; Zhang, Youjun (Frontiers in Physiology, 2020)
The olfactory system serves a vital role in the evolution and survival of insects, being involved in behaviors such as host seeking, foraging, mating, and oviposition. Odorant-binding proteins (OBPs) and chemosensory proteins (CSPs) are involved in the olfactory recognition process. In this study, BtabCSP11, a CSP11 gene from the whitefly Bemisia tabaci, was cloned and characterized. The open reading frame of BtabCSP11 encodes 136 amino acids, with four highly conserved cysteine residues. The temporal and spatial expression profiles showed that BtabCSP11 was highly expressed in the abdomens of B. tabaci females. Dietary RNA interference (RNAi)-based functional analysis showed substantially reduced fecundity in parthenogenetically reproduced females, suggesting a potential role of BtabCSP11 in B. tabaci reproduction. These combined results expand the function of CSPs beyond chemosensation.